QOLP-17. FACTORS ASSOCIATED WITH PSYCHOLOGICAL DISTRESS IN CAREGIVERS OF PATIENTS WITH MALIGNANT GLIOMAS. (11th November 2019) - Landay, Sophia; Anand, Maya; Horick, Nora; Jacobs, Jamie; Quain, Kit; Temel, Jennifer; Forst, Deborah
Abstract: BACKGROUND: Caregivers of patients with newly diagnosed malignant gliomas experience high rates of psychological distress. However, the factors associated with distress in this population have not been well described. We sought to evaluate patient-related, caregiver-related and tumor-related factors associated with depression and anxiety in this caregiver population. METHODS: We conducted a prospective study in patients with newly diagnosed malignant gliomas and their caregivers, collecting self-report data within 6 weeks of diagnosis. Patients' and caregivers' depression and anxiety were assessed using the Hospital Anxiety and Depression Scale, with subscale scores >7 considered clinically significant. Information about the tumor location and molecular features was extracted from the medical record. We used univariate and multivariate linear models to evaluate the association between caregiver anxiety and depression at baseline and specific caregiver-, patient- and tumor-related factors. RESULTS: We enrolled 61 patient-caregiver dyads in this study. 26.2% (16/61) of caregivers had significant depression symptoms, and 47.5% (29/61) had significant anxiety. In the multivariable analysis, factors associated with higher caregiver depression score included younger caregiver age (< 65 years old; B=4.24, p=0.0002), left-sided tumor location (B=1.98, p=0.030), IDH wild-type tumor status (B=3.44, p=0.0008) and patient anxiety (B=2.28, p=0.017). Factors associated with higher caregiver anxiety were younger caregiver age (B=2.47, p=0.089) and left-sided tumor location (B=4.23, p=0.001). CONCLUSIONS: Younger caregiver age and caring for a patient with a tumor on the left side of the brain were associated with worse caregiver depression and anxiety. Higher caregiver depression was correlated with caregivers whose loved one had significant anxiety or had an IDH wild-type tumor. Understanding the factors associated with caregiver anxiety and depression may guide neuro-oncology clinicians in identifying caregivers who may be at an increased risk for psychological distress at the time of their loved one's diagnosis, allowing for earlier initiation of support services for these caregivers.